The Urgency of Increase in Judges' Salaries and Fair Decisions - Nani Widya Sari; Guntarto Widodo; Oksidelfa Yanto; Isnu Harjo Prayitno; Rifka Zuwanda (International Journal of Law and Society, 2025)
This research will analyze the increase in judges' salaries and its impact on fair decisions for justice seekers. Furthermore, it also aims to analyze what aspects need to be considered to achieve the ideal goal of the criminal justice process so that judges' decisions can fulfill a sense of justice. The method used in this study is the normative juridical writing method using secondary data obtained through literature study. The results of the study indicate that with an adequate salary increase, judges can focus more on their duties to provide fair decisions and are not tempted by external factors that can affect their independence. In addition, there are several aspects that need to be considered so that the criminal justice process can produce decisions that fulfill a sense of justice, including decisions must be based on the principle of substantive justice, namely justice that considers the material aspects of the case, not just formal procedures. Then there is also consistent application of the law, transparency and accountability. And no less important is respect for human rights. Thus, increasing judges' salaries can be one effort to improve the quality of law enforcement and justice in Indonesia.